A STUDY ON SELECTION OF PROMISING NATIVE CHERRY LAUREL (PRUNUS LAUROCERASUS L.) GENOTYPES FROM SAKARYA, TURKEY - O. Beyhan (Journal of Animal and Plant Sciences, 2010)
This study was carried out to select cherry laurel (Prunus laurocerasus L.) genotypes grown in Akyazi district of Sakarya province (northwest Turkey) during 2008-2009. Ten laurel cherry genotypes were selected based on their phenological, pomological and morphological characteristics. The flowering time of promising genotypes started in the first week of March and continued to the end of month. Harvesting started from the first week of July to the last week of October. Fruit weight of promising genotypes ranged between 1.08 to 5.33 g, while cluster weight showed a range of 21.60 to 109.27 g, with 19.06 to 27.00 number of fruits per cluster having stone weight of 0.220 to 0.546 g. The soluble solid content varied between 16.00 to 22.00 % with, pH value of 4.63 to 4.92 of the fruit juice.
Keywords: Cherry laurel; phenology; pomology; selection